PENGARUH MODAL, TENAGA KERJA, DAN BAHAN BAKU TERHADAP PENDAPATAN PENGRAJIN GERABAH DESA MELIKAN, KABUPATEN KLATEN - Mei Sulistyaningsih; Eko Triyanto (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to analyze the influence of capital, labor and raw materials on MSME income. The object of this research focuses on pottery craftsmen in Melikan Village, Wedi District, Klaten Regency. There are several factors that influence income such as the amount of capital, labor, and raw materials. The sampling technique in this research is non-probability sampling using purposive sampling technique. The approach used is a quantitative approach and uses a case study type of research. By using the Slovin formula, a population of 201 craftsmen and an error limit of 10 percent, a sample of 67 craftsmen was obtained. The results of this research show that partially capital has a significant effect on income. Labor does not have a significant effect on Income and Raw Materials do not have a significant effect on Income. Capital, Labor and Raw Materials simultaneously influence Income.